Teaching history with newsreels and public service shorts - Gulyas, Aaron John, 1975- (Teaching history with ... series, 2017)
This volume serves as a guide for teaching history with newsreels and short subject nonfiction films. In addition to introducing teachers of history to the wide range of short films available for classroom use, this volume provides sample lesson plans, assessment activities, and discussion guides.